Analysis of Influence Factors of Negative Skin Friction on PHC Pile in High-Backfill Sites - Gen, Xiong; Ben, He; Bing, Pan; Xiangming, Ge; Weijiang, Chu (Frontiers in Physics, 2022)
It is recognized that the negative skin friction (NSF) on a pile affects the structural and geotechnical design. The influence factors on the formation of NSF on a pre-stressed high-strength concrete (PHC) pipe pile under a control building in a Vietnamese project were investigated using a numerical model in FLAC3D, which was verified by a pile loading test onsite. The height of backfills, the consolidation degree of soil, working loads on the PHC pipe pile, and the pile diameter were analyzed in sensitivity analyses. It was found that the height of backfills and the consolidation degree were dominant in the formation of NSF, an increase of the dragload, and the position of the neutral plane. The working load and the pile diameter affected the dragload and the position of the neutral plane less. A limit decrease of the dragload induced by NSF can be observed when the working load increased. One engineering compromise was to accelerate the consolidation process for decreasing NSF and improving the performance of the PHC pipe pile.